Osteoarthritis of the hand. Natural treatment based on Boswellia serrata, Zingiber officinale, Turmeric, Willow bark, Capsaicin and Green lipped muscles from New Zealand: a study of strength, movement and pain - Lanzetta, Marco (Progress in Nutrition, 2014)
A case study on 25 patients suffering from thumb basal joint osteoarthritis is presented. A treatment based on natural supplements was compared to a more conventional drug-based scheme. The results were in favour of the more natural treatment when strength, movement and pain were assessed. The lack of side effects was particularly interesting.